Lower class people suffered more (but perceived fewer risk disadvantages) during the COVID‐19 pandemic - Zhang, Yue; Ding, Yi; Xie, Xiaona; Guo, Yongyu; Lange, Paul A. M. (Asian journal of social psychology, 2023)
Does COVID‐19 affect people of all classes equally? In the current research, we focus on the social issue of risk inequality during the early stages of the COVID‐19 pandemic. Using a nationwide survey conducted in China (N = 1,137), we predicted and found that compared to higher‐class individuals, lower‐class participants reported a stronger decline in self‐rated health as well as economic well‐being due to the COVID‐19 outbreak. At the same time, we examined participants' beliefs regarding the distribution of risks. The results demonstrated that although lower‐class individuals were facing higher risks, they expressed lesser belief in such a risk inequality than their higher‐class counterparts. This tendency was partly mediated by their stronger endorsement of system‐justifying beliefs. The findings provide novel evidence of the misperception of risk inequality among the disadvantaged in the context of COVID‐19. Implications for science and policy are discussed.